(untitled) (Acta Scientiarum. Biological Sciences, 2011)
The reproductive system of male Phrynops geoffroanus adults is macroscopically described and the variation in testicular biometry is evaluated. A pair of oval testes is connected by the efferent ductules to the epididymis, which continue as deferent ducts, which emerge in the penis. The volume of the gonads showed the highest averages during spring and summer months. GSI varied significantly throughout the year, with the highest averages observed in the months that correspond to the end of spring and the beginning of summer, when the reproduction of the species takes place, and the lowest averages were seen in winter, suggesting a cyclical testicular activity.